2015
DOI: 10.1007/s00706-015-1553-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure, spectral, dielectric characteristics and conduction mechanism of two novel carboxylates of 1-benzhydrylpiperazine

Abstract: Two new 1-benzhydrylpiperazinium carboxylates with tartrate and maleate, (C 17 H 21 N 2 )(C 4 H 5 O 6 ) and (C 17 H 22 N 2 )(C 4 H 3 O 4 ) 2 , have been synthesized and characterized. Crystal structure determinations show that the compounds crystallize in the P2 1 and the P2 1 /c space groups of the monoclinic system, respectively. Only in the maleate the organic group is protonated on both nitrogen atoms of piperazine ring. The infrared spectra of these compounds reported from 400 to 4000 cm -1 confirmed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…The disc diffusion method showed that, the effect of both the trans-2,5 dimethylpiperazine Fig.17. Our results join many previous researches, where the antibacterial activity of newly synthesized compound depends on the membrane structure [45]. The difference of sensitivity, found between Gram-positive and Gram-negative bacteria to the the trans-2,5 dimethylpiperazine and our newly synthetized compound can be attributed to the outer membrane of Gram-negative bacteria that usually forms a physical barrier to most antibiotic.…”
Section: Biological Studysupporting
confidence: 88%
“…The disc diffusion method showed that, the effect of both the trans-2,5 dimethylpiperazine Fig.17. Our results join many previous researches, where the antibacterial activity of newly synthesized compound depends on the membrane structure [45]. The difference of sensitivity, found between Gram-positive and Gram-negative bacteria to the the trans-2,5 dimethylpiperazine and our newly synthetized compound can be attributed to the outer membrane of Gram-negative bacteria that usually forms a physical barrier to most antibiotic.…”
Section: Biological Studysupporting
confidence: 88%